2018
DOI: 10.5326/jaaha-ms-6550
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of English Bulldogs with Presumed Arrhythmogenic Right Ventricular Cardiomyopathy: 31 Cases (2001–2013)

Abstract: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an important cause of sudden death in people and boxer dogs that has recently been described in English bulldogs. The objective of this retrospective study was to describe the clinical characteristics of English bulldogs with presumed ARVC. The medical records were searched for English bulldogs examined between 2001 and 2013 with a clinical diagnosis of ARVC. The average age of the 31 dogs identified was 9.2 ± 1.6 yr (range 7-13 yr). Males were overrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
10
0
3
Order By: Relevance
“…In accordance, some breeds like Boxers and Bulldogs that have among the strongest founder events in our analysis are also known to be affected by high rates of genetic disorders. For instance, arrhythmogenic right ventricular cardiomyopathy that is a cardiac disease causing sudden death is seen at high frequency in both breeds 63,64 . The temporal distribution of founder events in dogs (~75-125 years ago) overlaps with the Victorian era when a large number of modern dog breeds were created in Great Britain in the context of popularizing dog-fancying and showing 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, some breeds like Boxers and Bulldogs that have among the strongest founder events in our analysis are also known to be affected by high rates of genetic disorders. For instance, arrhythmogenic right ventricular cardiomyopathy that is a cardiac disease causing sudden death is seen at high frequency in both breeds 63,64 . The temporal distribution of founder events in dogs (~75-125 years ago) overlaps with the Victorian era when a large number of modern dog breeds were created in Great Britain in the context of popularizing dog-fancying and showing 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of the dogs were reported “unknown breed”, 62 mixed breeds, and the remaining were named by breed. Of 305 dogs that had breeds listed ( Figure 3 ), 223 (73%) were identified as a breed predisposed to DCM (Golden Retrievers, Great Danes, Doberman Pinschers, Boxers, Cocker Spaniels, and Bulldogs) ( Calvert et al, 1997 ; Kittleson et al, 1997 ; Sisson et al, 2000 ; Broschk and Distl, 2005 ; Domanjko-Petric and Tomsic, 2008 ; Cunningham et al, 2018 ; Kaplan et al, 2018 ). Overrepresentation and breed reporting bias possibly inflated the number of reported cases ( FDA, 2019a ).…”
Section: Limitations To Current Fda Reportsmentioning
confidence: 99%
“…Currently, no STRN mutation for human ACM patients is listed in the HGMD or the ARVD/C Genetic Database 4 . In addition, ACM was described for English Bulldogs and Weimaraners (Eason et al, 2015;Cunningham et al, 2018). Corresponding to Boxer ACM, it was shown that ACM presented with right-ventricular dilation, thin right-ventricular wall diameter, ventricular tachycardia, and severe fibro-fatty replacement of the 4 https://molgenis136.gcc.rug.nl myocardium, which occurred spontaneously in domestic cats (Fox et al, 2000;Harvey et al, 2005;Ciaramella et al, 2009).…”
Section: Acm Animal Models Without Human Genetic Correlationmentioning
confidence: 99%